2022
DOI: 10.1107/s160057752101198x
|View full text |Cite
|
Sign up to set email alerts
|

Covalency between the uranyl ion and dithiophosphinate by sulfur K-edge X-ray absorption spectroscopy and density functional theory

Abstract: The dithiophosphinic acids (HS2PR 2) have been used for the selective separation of trivalent actinides (AnIII) from lanthanides (LnIII) over the past decades. The substituents on the dithiophosphinic acids dramatically impact the separation performance, but the mechanism is still open for debate. In this work, two dithiophosphinic acids with significantly different AnIII/LnIII separation performance, i.e. diphenyl dithiophosphinic acid (HS2PPh2) and bis(ortho-trifluoromethylphenyl) dithiopho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 80 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…5 This combination of DFT and spectroscopy has also been employed to study covalency in actinide ligand bonds by several other groups. 6–11 Furthermore, experiment has also validated the use of QTAIM parameters to measure covalency; for example, changes in chemical shifts in both 13 C and 15 N nuclear magnetic resonance (NMR) spectra show good correlation with bond order metrics, for a range of actinide ligand bonds. 12,13…”
Section: Introductionmentioning
confidence: 96%
“…5 This combination of DFT and spectroscopy has also been employed to study covalency in actinide ligand bonds by several other groups. 6–11 Furthermore, experiment has also validated the use of QTAIM parameters to measure covalency; for example, changes in chemical shifts in both 13 C and 15 N nuclear magnetic resonance (NMR) spectra show good correlation with bond order metrics, for a range of actinide ligand bonds. 12,13…”
Section: Introductionmentioning
confidence: 96%
“…To ascertain that O1 connected to U originates from the methanol molecule, we measured the C–O bond length of O1, which is 1.431(5) Å (Table S2). This discrepancy may be attributed to charge attraction subsequent to coordination with the metal . The stretching vibration in the IR spectrum at 3500 cm –1 in Figure S2 can also be attributed to the −OH group originating from the coordinating methanol .…”
mentioning
confidence: 96%
“…23 This discrepancy may be attributed to charge attraction subsequent to coordination with the metal. 24 The stretching vibration in the IR spectrum at 3500 cm −1 in Figure S2 can also be attributed to the −OH group originating from the coordinating methanol. 25 In the axial position, occupied by two acyl oxygen atoms, the uranium atomic center forms a seven-coordinated pentagon−bipyramidal coordination geometry between O and S atoms, as shown in Figure 1b.…”
mentioning
confidence: 97%
“…(2) Alexander Scott Ditter and co-authors showed the power of soft X-ray spectromicroscopy at the O K-, U N 4,5 -and Ce M 4,5 -edges for spent nuclear fuel investigations, yielding chemical information on the sub-micrometre scale (Ditter et al, 2022). Yusheng Zhang and co-workers investigated the covalency effects in the bonding between the uranyl ion and dithiophosphinate by combining sulfur K-edge XANES and density functional theory (Zhang et al, 2022).…”
mentioning
confidence: 99%